2019
DOI: 10.1111/jocd.12892
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐damaged evaluation of virgin hair

Abstract: Summary Background Hair‐straightening treatments may involve the use of thermal devices, which potentially cause damages in the cuticle and cortex of the hair fibers. Particularly, the heat causes denaturation of the α‐keratin and the degradation of the components of the hair cortex. Objectives The aim of this study was to evaluate the effect of heating on the cuticle and cortex of the Caucasian and Asian virgin hair by using heat iron flat. Methods The effects of the heating in the tresses of Caucasian and As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
(55 reference statements)
0
12
0
5
Order By: Relevance
“…Experimental studies have shown that exposure of heat (either through thermal devices or atmospheric heat) may result in the denaturation of alpha-keratin and change the structure of the hair cuticle. [ 26 27 28 ] These changes may differ according to the ethnicity of individuals; this is due to the difference in anatomical structure and hair composition in these ethnic groups. For example, Asian hair is circular, has a higher number of cuticle layers, and is compact compared with Caucasian hair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies have shown that exposure of heat (either through thermal devices or atmospheric heat) may result in the denaturation of alpha-keratin and change the structure of the hair cuticle. [ 26 27 28 ] These changes may differ according to the ethnicity of individuals; this is due to the difference in anatomical structure and hair composition in these ethnic groups. For example, Asian hair is circular, has a higher number of cuticle layers, and is compact compared with Caucasian hair.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Asian hair is circular, has a higher number of cuticle layers, and is compact compared with Caucasian hair. [ 27 29 ] Furthermore, even though the chemical composition is similar in different hair types, African hair has less moisture. [ 29 30 31 ] Though, in general, alternate heat and wet cycles result in cracks in hair cuticle; the loss of protein and changes in the cuticle were more in the Asian hair compared with the Caucasian hair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 It can cause the denaturation of the α-keratin and the degradation of the hair cortex components. 10 The weakening of the fiber occurs as the rearrangement of the disulfide bonds leads to structural damage, protein loss, 8 and decrease in tensile strength. 11,12 The bleaching process is intended to induce extensive breakdown of the hair pigments, pheomelanin, and eumelanin.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Coroaba A et al [1] used scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and other physical and chemical methods to identify the effects of alopecia areata on the structure and composition of human hair. Lima et al [2] used a heating iron to heat hair and observed hair images under a scanning electron microscope to evaluate the damage to the epidermis and cortex of the hair fiber by heat loss. Although these manual methods use scanning electron microscope imaging technology to analyze hair microscopic images, they do not perform detailed quantitative classification of hair damage.…”
Section: Introductionmentioning
confidence: 99%